We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
179
1
avatar

8-(2+1)+3 to the power of 2

 Jan 31, 2018

Best Answer 

 #1
avatar
+1

8-(2+1)+3 to the power of 2

 

[8 - (2+1) + 3]^2 =

[8 - 3 + 3]^2 =

[5 + 3]^2 =

8^2 = 64

 Jan 31, 2018
 #1
avatar
+1
Best Answer

8-(2+1)+3 to the power of 2

 

[8 - (2+1) + 3]^2 =

[8 - 3 + 3]^2 =

[5 + 3]^2 =

8^2 = 64

Guest Jan 31, 2018

7 Online Users

avatar